2016
DOI: 10.1039/c5md00376h
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the trehalose utilization pathways ofMycobacterium tuberculosis

Abstract: Tuberculosis (TB) is an epidemic disease and the growing burden of multidrug-resistant (MDR) TB world wide underlines the need to discover new drugs to treat the disease. Mycobacterium tuberculosis (Mtb) is the etiological agent of most cases of TB. Mtb is difficult to treat, in part, due to the presence of a sturdy hydrophobic barrier that prevents penetration of drugs through the cell wall. Mtb can also survive in a non-replicative state for long periods of time avoiding the action of common antibiotics. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 112 publications
0
48
0
1
Order By: Relevance
“…As discussed recently, trehalose metabolism has received increasing attention as a target for the development of novel anti-tubercular agents. [3,4] Trehalose ( 1 ), a non-mammalian disaccharide, is essential for mycobacterial viability and virulence. Trehalose is responsible for the transport of mycolic acids—long-chain (C 60 –C 90 ), α-branched, β-hydroxy fatty acids—to the exterior of the cell, where they are used to construct the thick, hydrophobic mycobacterial outer membrane, or “mycomembrane.”[5] As shown in Figure 1, cytoplasmic trehalose is converted to trehalose monomycolate (TMM),[6] which is then transported across the plasma membrane by MmpL3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed recently, trehalose metabolism has received increasing attention as a target for the development of novel anti-tubercular agents. [3,4] Trehalose ( 1 ), a non-mammalian disaccharide, is essential for mycobacterial viability and virulence. Trehalose is responsible for the transport of mycolic acids—long-chain (C 60 –C 90 ), α-branched, β-hydroxy fatty acids—to the exterior of the cell, where they are used to construct the thick, hydrophobic mycobacterial outer membrane, or “mycomembrane.”[5] As shown in Figure 1, cytoplasmic trehalose is converted to trehalose monomycolate (TMM),[6] which is then transported across the plasma membrane by MmpL3.…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been used to develop inhibitors targeting trehalose metabolism, including the rational design of trehalose-based inhibitors. [3] The first example of a trehalose-based inhibitor was reported by Belisle and co-workers, who observed that 6-azido-6-deoxy-α,α′-trehalose (6-TreAz, 8 ) inhibited growth of M. aurum on solid medium (MIC 200 μg/mL). [10] Treatment of M. aurum with a sub-inhibitory concentration of 6-TreAz led to marked reductions in TMM, TDM, and AGM, suggesting that the compound indeed acted on trehalose-mediated mycolic acid export.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the recent progress in this area was covered in a 2016 review by Thanna and Sucheck. 116 Other prokaryotic pathogens also have trehalose metabolic pathways involved in physiology and pathogenesis. 8,9 The importance of trehalose metabolism to insects 3 may provide opportunities for the development of new insecticides.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 99%
“…Indeed, HTS-based searches for anti-mycobacterial compounds have yielded numerous drug-like small molecules that act on trehalose metabolism, some of which are presently being pursued as possible treatments for tuberculosis. 116 Another approach that has shown promise is the rational design of inhibitors based on the structure of trehalose or trehalose derivatives. In keeping with the theme of this review, here we discuss the synthesis and evaluation of trehalose-based inhibitors in mycobacteria and other systems.…”
Section: Applications Of Trehalose Analoguesmentioning
confidence: 99%
“…Изучаются воз-можности трегалозы в восстановлении функции повреждённых белковых молекул при болезни Альцгеймера и хорее Хантингтона [41]. Фермен-ты патогенных микроорганизмов, отвечающие за синтез трегалозы, становятся мишенями для разработки принципиально новых противогрибко-вых и противотуберкулёзных препаратов [37,42]. Способность трегалозы надёжно защищать кле-точные мембраны от повреждающего воздействия низких температур нашла применение в криокон-сервации ооцитов (ЭКО), трансплантации кле-ток и тканей (гепатоцитов, панкрео цитов) [41].…”
unclassified